Proceedings of the International Conference on Health and Medical Sciences (AHMS 2020) 2021
DOI: 10.2991/ahsr.k.210127.018
|View full text |Cite
|
Sign up to set email alerts
|

Overview: Application of Carbopol 940 in Gel

Abstract: Carbopol is an acrylic polymer. Carbopol is non-toxic and non-irritating so that it is suitable for gel preparations. Carbopol 940 is often used as a gelling agent in gel preparations. Concentration of carbopol 940 as a gelling agent needs to be concerned to obtain a good gel preparation. This study aimed to determine the effect of carbopol 940 concentration on physical properties, drug release and the use in eye drops. The research method used was descriptive method with data collection technique using PICO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…For instance, different grades of CP were formulated in a study to deliver meloxicam, and it was found that none of the formulation prepared in the study demonstrated pharmaceutical instability problems during accelerated stability testing [ 54 ]. However, there are studies that support that a change in the pH of the CP-based gel formulations during the stability study can impart change in the viscosity of the formulations [ 55 ]. Nevertheless, the pH of the optimized formulation in the current study did not change significantly over time ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, different grades of CP were formulated in a study to deliver meloxicam, and it was found that none of the formulation prepared in the study demonstrated pharmaceutical instability problems during accelerated stability testing [ 54 ]. However, there are studies that support that a change in the pH of the CP-based gel formulations during the stability study can impart change in the viscosity of the formulations [ 55 ]. Nevertheless, the pH of the optimized formulation in the current study did not change significantly over time ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is a hydrophilic, non-toxic, and non-irritating synthetic polymer often used in the pharmaceutical industry as a base for soft dosage forms. The advantage of this polymer is its ability to form gels in water at room temperature within a wide pH range (from 4 to 10) [ 45 ]. The amount of Carbopol ® 940 affects the consistency of the composition [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…It's because Formula 1 and 3 contain less gelling agent (1.0% of Carbopol). It is known that the lower concentration of Carbopol will increase the gel capability to spread [28]. On the other side, the viscosity of Formula 1 and 3 are lower than Formula 2 and 4.…”
Section: Spreadability and Viscosity Testmentioning
confidence: 97%
“…In order for a wound-healing preparation to assist this process, its pH must not be more than 6.0. Carbopol as the gelling agent, naturally has acidic pH, so it needs to be neutralized to reach the targeted pH of formulation [28]. Triethanolamine (TEA) as the pH adjuster plays the important role to alkalize the gel's pH.…”
Section: Organoleptic and Phmentioning
confidence: 99%